Sinterização por métodos não convencionais e propriedades magnetoelétricas de compósitos nanoestruturados (1-x)BaZr₀‚₀₈Ti₀,₉₂O₃/(x)CoFe₂O₄ (0,10 ≤ x ≤ 0,50) livres de chumbo - Caminata, Laís Pacheco (2023)
Lead-free magnetoelectric composites have been widely investigated due to the current need for new potential applications in miniaturized devices. To this end, developing nanostructured materials and exploring their properties have attracted interest in the scientific field. In this context, the objectives of this thesis are obtaining nanostructured magnetoelectric particulate composites based on the system (1-x)BaZr0.08Ti0.92O3/(x)CoFe2O4 (BZT/CFO) (0.10≤x≤0.50), and analyzing their properties. For this purpose, nanopowders of the biphasic composites synthesized by the one-pot Pechini method assisted by microwave were used in the conventional sintering (CS), microwave-assisted sintering (MWS), and Spark Plasma Sintering (SPS). In an unprecedented way for this system, in addition to the concomitant study of the three sintering methods (CS, MWS, and SPS), the sintering kinetics for densification in the initial stage were evaluated. It was established that the activation energy for densification of the biphasic composite with a higher content of BZT (80BZT/20CFO) is higher than the composite with a higher content of CFO (50BZT/50CFO). The density values for all biphasic composites were higher than 91%, mainly influenced by the CFO content. The XRD structural analysis confirmed the presence of both BZT and CFO phases for 0.20≤x≤0.50, and small traces of spurious phases are predominant in composites sintered by CS and for lower proportions of CFO. Micrograph analysis confirmed the success in obtaining nanostructured composites, with significantly smaller values of average grain sizes provided by MWS and SPS sintering. The multiferroic properties were analyzed by ferroelectric and magnetic hysteresis loops. The coupling between the ferroic orderings was successfully verified for the nanostructured composites (1-x)BZT/(x)CFO (0.20≤x≤0.50). The highest values of magnetoelectric coefficients were observed for 80BZT/ 20CFO-CS and 50BZT/50CFO for MWS and SPS.